Subcutaneous abscess caused by Trueperella pyogenes in a Southern pudu (Pudu puda) - Llanos-Soto, Sebastián; González-Muñoz, Paulina; Opazo-Capurro, Alexis; González-Rocha, Gerardo; González-Acuña, Daniel (Austral Journal of Veterinary Sciences, 2020)
A case of an abscess on the head of a captive Southern pudu (Pudu puda) caused by Trueperella pyogenes is described. A diagnosis was done based on bacterial culture and MALDI-TOF MS identification. Traumatic inoculation of the bacterium in the subcutaneous tissue is speculated.